2020
DOI: 10.24207/jca.v33i3.3403
|View full text |Cite
|
Sign up to set email alerts
|

The Electrocardiogram in the Differential Diagnosis of Cardiologic Conditions Related to the COVID-19 Pandemic

Abstract: The World Health Organization (WHO) declared Sars-CoV infection and COVID-19 as a pandemic and global emergency. In addition to viral pneumonia and the severe acute respiratory syndrome (Sars), the heart is affected in some patients due to the detection of biomarkers and reported cases of myocarditis and pericarditis. Therefore, the knowledge of electrocardiogram presentation of these actual infections can guide the choice for the best treatment and can help to reduce misdiagnosis, mainly the acute myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The pathophysiology is associated with high plasma levels of catecholamines, the impact of adrenergic activity on cardiac myocytes causing ascending ST-segment elevation and J point depression. Moreover, high catecholamine levels might increase oxygen demand, inducing vasospasm and myocardial injury, patients with SARS-CoV-2 infection being exposed to a high endogenous secretion as a compensatory intravenous infusion, which are used as a therapeutic method [ 23 , 129 ]. Another determinant mechanism involves the hypothalamic-pituitary-adrenal (HPA) axis, which is activated in COVID-19; several studies have shown that cortisol and adrenocorticotrophic hormones were dysregulated.…”
Section: Electrocardiographic Changes In Myocardial Ischemia In Covid...mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology is associated with high plasma levels of catecholamines, the impact of adrenergic activity on cardiac myocytes causing ascending ST-segment elevation and J point depression. Moreover, high catecholamine levels might increase oxygen demand, inducing vasospasm and myocardial injury, patients with SARS-CoV-2 infection being exposed to a high endogenous secretion as a compensatory intravenous infusion, which are used as a therapeutic method [ 23 , 129 ]. Another determinant mechanism involves the hypothalamic-pituitary-adrenal (HPA) axis, which is activated in COVID-19; several studies have shown that cortisol and adrenocorticotrophic hormones were dysregulated.…”
Section: Electrocardiographic Changes In Myocardial Ischemia In Covid...mentioning
confidence: 99%
“…The ECG changes in myocardial ischemia include a broad spectrum in patients with COVID-19, different cases of ST-segment elevation, ST-segment depression, and T-wave inversion being reported, which were associated with a severe form of COVID-19 disease [ 21 , 22 ]. Several authors have described P-wave changes, in the context of atrial infarction, which is supplied in 60% of cases by the right coronary artery and in 40% by the circumflex artery through the superior ramus ostium cava [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes could be noticed in the electrocardiogram (ECG) of COVID-19 cases. Those Cardiac alterations [ 38 , 39 ] have encouraged the examination of ECG as a diagnostic tool for COVID-19 diagnosis. Taking into consideration the great benefits of ECG usage such as portability, availability, ease of use, inexpensive, harmlessness, real-time examination, the automatic diagnosis of COVID-19 from ECG can be of substantial importance besides PCR tests and chest X-ray or CT scans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the respiratory system, COVID-19 infection may affect the cardiovascular system [ 9 ]. Several cardiovascular abnormalities can be seen in COVID-19 patients [ 10 , 11 ] that may manifest as cardiac arrhythmia, conduction problems, ECG abnormalities, myocarditis, and pericarditis [ 12 ]. ST changes on ECG offer clues to COVID-19 diagnosis that may denote subclinical or clinical cardiovascular injury [ 13 ].…”
Section: Introductionmentioning
confidence: 99%